NOMOPHOBIA DALAM PERSPEKTIF MEDIA, BUDAYA DAN TEKNOLOGI - Hardianti, Fitri (EDUTECH, 2019)
Nomophobia is an abbreviation of "No Mobile Phone Phobia" which is a concern that arises when it is far from its Mobile Phone. Those who have a tendency to suffer from nomophobia will be overwhelmed with anxiety when away from their Mobile Phone so they will always try to be close to their Mobile Phone. This can certainly be a psychiatric disorder and can even have an aggressive impact on others if you don't find the Mobile Phone with him. The purpose of this research is to find out the meaning of nomophobia in the perspective of media, culture and technology from the point of view of students who have nomophobic tendencies. The method used in this study is qualitative with a phenomenological approach. Data collection techniques used were in-depth interviews. The data analysis technique uses miles and huberman interactive model analysis. And the data validity technique in this study uses source triangulation. The results of this study are that it is known that there is a close connection between Nomophobia and the perspective of media, culture and technology. As for the meaning, rituals and motives of a person in using Mobile Phone is different. Among the meanings of the informants regarding Mobile Phone, namely: there are those who interpret it as a source of information, some say as a tool that connects with other people, and there are also those who interpret it as a source of income. As for the self-ritual of students with nomophobic tendencies where they are daily dependent on the presence of mobile phones, whether it is to seek information, related to work and so on. And besides, their motives for using Mobile Phone can be concluded that is related to the need for technology in facilitating their daily work.Nomophobia adalah singkatan dari "No Mobile Phone Phobia" yang merupakan kekhawatiran yang muncul ketika jauh dari Handphone-nya. Mereka yang memiliki kecenderungan menderita nomophobia akan diliputi rasa cemas saat jauh dari Ponselnya sehingga mereka akan selalu berusaha dekat dengan Ponselnya. Hal ini tentunya bisa menjadi gangguan kejiwaan dan bahkan bisa berdampak agresif pada orang lain jika tidak menemukan Handphone bersamanya. Tujuan dari penelitian ini adalah untuk mengetahui makna nomophobia dalam perspektif media, budaya dan teknologi dari sudut pandang siswa yang memiliki kecenderungan nomophobia. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan fenomenologis. Teknik pengumpulan data yang digunakan adalah wawancara mendalam. Teknik analisis data menggunakan analisis model interaktif miles dan huberman. Dan teknik keabsahan data dalam penelitian ini menggunakan triangulasi sumber. Hasil penelitian ini diketahui bahwa ada hubungan erat antara Nomophobia dengan perspektif media, budaya dan teknologi. Adapun makna, ritual dan motif seseorang dalam menggunakan Handphone berbeda-beda. Diantara pengertian informan mengenai Handphone yaitu : ada yang mengartikan sebagai sumber informasi, ada yang mengatakan sebagai alat penghubung dengan orang lain, dan ada juga yang mengartikan sebagai sumber pendapatan. Adapun ritual diri siswa dengan kecenderungan nomophobic dimana mereka sehari-hari bergantung pada keberadaan handphone, baik itu untuk mencari informasi, berhubungan dengan pekerjaan dan lain sebagainya. Selain itu, motif mereka dalam menggunakan Handphone dapat disimpulkan terkait dengan kebutuhan akan teknologi dalam mempermudah pekerjaan sehari-hari mereka.